The history of rome : from earliest times to the establishment of the Empire - Smith, William (Andrews UK Ltd., 2010)
This detailed history of Rome covers from the earliest times (including the foundation of the city) to the establishment of the Empire, and has been specially formatted for today's e-book readers. Featuring many illustrations, including coins, buildings, busts and more, this excellent book is one of the most well respected within the classical civilisation field. Subject matters covered include politics, architecture, day-to-day life and much more. The book is written in an educational style, full of interesting facts and detailed analysis.